Conditions for Oscillation of a Neutral Differential Equation - Weiping Yan; Jurang Yan (International Journal of Differential Equations)
For a neutral differential equation with positive and changeable sign coefficients [x(t)−a(t)x(δ(t))]′+p(t)F(x(τ(t)))−q(t)G(x(σ(t)))=0, oscillation criteria are established, where q(t) is not required as nonnegative. Several new results are obtained.